Edukasi "Jagoan Cilik: Berani Baik dan Cerdas Berinternet" sebagai Upaya Pencegahan Bullying dan Peningkatan Literasi Digital pada Siswa Sekolah Dasar - Auliyaur Rabbani; Cindy Berliana Febriyanti; Devi Ayu Firnanda; Achmad Nur; Nadia Surya Yunita (Journal Of Human And Education (JAHE), 2026)
The development of digital technology provides many benefits for elementary school children, especially a medium for learning, communication, and accessing information. However, on the other hand, the ease of internet access also increases the risk of technology misuse, such as exposure to negative content, personal data breaches, and bullying, both directly and through digital media (cyberbullying). This condition highlights the importance of providing education from an early age so that students can use the internet safely, wisely, and responsibly while developing a respectful and caring attitude toward others. This community service activity aims to improve the knowledge and awareness of sixth-grade elementary school students regarding bullying prevention and healthy internet use through the Little Champions: Dare to Be Kind & Smart on the Internet program. The method used was interactive educational sessions involving students active participation through educational games, presentations, discussions, simple simulations, quizzes, and reflection using the Commitment Tree. The activity was conducted at Kedungsukodani Elementary School, Balongbendo District. Sidoarjo Regency, for 90 minutes. The results showed that students were able to identify various forms of bullying, understand its impact on victims, recognize preventive measures, and apply the principles of safe intermet use, such as protecting personal data, avoiding suspicious links, using social media wisely, and managing screen time. Students enthusiasm throughout the activity indicated that interactive learning methods effectively improved their understanding, participation, and engagement. This program is expected to contribute to strengthening character education and digital literacy among elementary school students, thereby creating safe, comfortable, and child-friendly learning environment.